PEMURNIAN MINYAK JELANTAH MENGGUNAKAN ARANG AKTIF DARI SEKAM PADI - Samangun, Theresia; Nasrun, David; Iskandar, Taufik (eUREKA : Jurnal Penelitian Mahasiswa Teknik Sipil dan Teknik Kimia, 2017)
Cooking oil is a one of human basic needs, as a food prossesing ingredient. It is has a frying medium fonetion that its essential and increase, and generale a essential a side production its called the waste oil. This study proposed finaly the presentage of number peroxide and decrease number iodinein waste oil after absorben used. Another goal is to measure KOH liquid consentration on charcoal that alde to absorb waste oil as well. A paddy charcoal activated in KOH activator liquid with KOH consentrat 10 %, 15 %, and 20 %. It is filtred by filter paper then washe in aquadest level PH 7. It is dried in oven at room temperature to 400oc in 2 hours. A next step is the waste oil and active charcoal that have been mixed in a beaker glass which its absorbed by time variation at 20 hours, 22 hours, and 24 hours with Erlenmeyer after that . it is filtered and analyzed numbers peroxide and numbers iodine. The condution of study is waste oil using active charcoal of paddy alde to decrease of peroxide level at 66.67 % and iodine at 57.17 % . soaking submerged and activator level of active charcoal has influeneed oil furification result. Based on research result has proved that the optimal time is 20 hours with KOH consentration at 5 % and 10 %. Keywords: adsorption, used cooking oil, activated charcoal